PENYELESAIAN SENGKETA TERHADAP LINGKUNGAN HIDUP DI MASYARAKAT MELALUI MEJA HIJAU - Dewi, Seroja Kususma; Rini Diah Puri Handayani; Saputro, Dahvit Danang Adi (IDFoS Indonesia, 2022)
Litigation or non-litigation may be used to settle an environmental dispute in the environmental law court. the resolution of the environmental conflict through the legal system with a claim based on Article 1365 of the Civil Act and Article 87 of Act Number 32, 2009 about the Protection and Environmental Control. The absolute strict liability principle is applied to acts and/or conducts that use B3 disposal or that pose a substantial threat to the environment.